Reinforcing effects of cyclic expansion extrusion with an asymmetrical extrusion cavity (CEE-AEC) on pure magnesium - JinSheng Ji; Jie Zheng; YuSha Shi; Heng Zhang; ZhiMin Zhang; Yong Xue (Materials Research Express, 2021)
In this paper, a relatively novel severe plastic deformation method cyclic expansion extrusionwith an asymmetrical extrusioncavity (CEE-AEC) was carried out to prepare large-sized pure magnesium (Mg) with high comprehensive performance. Finite element analysis (FEM) was used to study the plastic deformation process and Electron Back-Scattered Diffraction (EBSD) was aimed to research the microstructural evolution. Three passes and isothermal deformation at 250 °C were chosen to satisfy the research. The central part of the billet was cut as the research area, and the resultant microstructure and mechanical properties were analyzed systematically. The results showed that the grain size was remarkably refined due to continuous dynamic recrystallization (CDRX) and discontinuous dynamic recrystallization (DDRX). Twins participated in the progress of deformation. The shear strain introduced by the asymmetrical extrusion cavity determined the formation of inclined basal texture, leading to the increasing value of basal 〈a〉 slip system Schmid factor. The best comprehensive tensile properties were obtained after three passes of deformation, and the contributions came from grain refinement strengthening and texture modification, respectively.